2015
DOI: 10.1161/circoutcomes.115.001751
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Referral and Enrolment Are Associated With Mitigated Benefits of Cardiac Rehabilitation After Coronary Artery Bypass Surgery

Abstract: Background-Cardiac rehabilitation (CR) is recommended after coronary artery bypass graft surgery; however, the consequences of longer wait times to start CR have not been elucidated. Method and Results-Cardiopulmonary, demographic, and anthropometric assessments were conducted before and after 6 months of CR in consecutively enrolled patients from January 1995 to October 2012. Wait times were ascertained from referral forms and charts. Neighborhood characteristics were ascertained using census data and cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 48 publications
3
62
0
1
Order By: Relevance
“…6 Factors associated with longer wait times for CR included female sex, older age, being employed, less social support, longer commute to CR, lower neighborhood socioeconomic status, higher systolic blood pressure, abdominal obesity and a complex medical history. In this study, longer wait times were not just associated with poorer adherence to CR, but also less improvement in cardiovascular fitness and cardiovascular risk reduction.…”
Section: Article See P 608mentioning
confidence: 99%
See 3 more Smart Citations
“…6 Factors associated with longer wait times for CR included female sex, older age, being employed, less social support, longer commute to CR, lower neighborhood socioeconomic status, higher systolic blood pressure, abdominal obesity and a complex medical history. In this study, longer wait times were not just associated with poorer adherence to CR, but also less improvement in cardiovascular fitness and cardiovascular risk reduction.…”
Section: Article See P 608mentioning
confidence: 99%
“…Marzolini et al 6 , in this issue of Circulation: Cardiovascular Quality and Outcomes, have identified another piece of the puzzle in accessing CR by investigating wait times. To date, the relationship between longer wait times and the commencement of CR has not been well described, and this analysis may elucidate how system-based factors can moderate access to evidence-based care and as a consequence health outcomes.…”
Section: Article See P 608mentioning
confidence: 99%
See 2 more Smart Citations
“…Omission of such basic data impact greatly on the interpretation of findings from studies (and reviews) as we cannot determine with accuracy the dose of exercise received. A delay in starting CR is associated with a decreased likelihood of uptake of CR [44]; it may also attenuate the benefits of CR for those who do attend [45]. Less than half of studies reported the time from event or surgery to start of CR [25,30,36,46].…”
Section: P=0046)mentioning
confidence: 99%